FINANCIAL HEALTH AND PERFORMANCE OF MERCHANT COOPERATIVE BANKS IN KARNATAKA: AN EMPIRICAL INVESTIGATION - Chowdappa R C; Devarajanayaka K M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the financial health and performance of merchant cooperative banks in Karnataka, focusing on key indicators such as profitability, asset quality, and operational efficiency. The primary purpose is to analyze the differences in financial performance across these banks and provide insights for improved management strategies. Using a descriptive research method and a convenience sampling technique, data was collected from 10 Merchant cooperative banks in Karnataka. Statistical tools like descriptive statistics and ANOVA were employed to analyze the results. The study finds significant variations in Net Profit, Return on Assets, Return on Equity, and Capital Adequacy Ratio among banks, indicating diverse financial health and performance levels. The findings suggest that banks with stronger capital reserves and better asset management exhibit superior profitability and customer satisfaction. The study underscores the need for improved risk management, capital enhancement, and customer-centric strategies for long-term sustainability.